Endovascular treatment of renal artery stenosis: Technical and clinical results [Renal arter darliklarinin stent ile endovasküler tedavisi: teknik ve klinik sonuçlar.] - (:unkn) unknown (My University, 2003)
PURPOSE: To determine the primary success rate and follow-up results of renal artery stenting in controlling renovascular hypertension and renal failure in patients with renal artery stenosis. MATERIALS AND METHODS: Balloon expandable stents were placed in 40 renal arteries of 35 patients (16 men, 19 women; mean age 60, 1). Indications for treatment were hypertension alone in 11 patients, disturbed renal functions alone in 12 patients and hypertension associated with renal failure in eight patients. Four of the patients were diagnosed during angiography due to peripheral arterial diseases. Blood pressures and serum creatinine levels were measured before the operation and after stenting. RESULTS: The primary technical success rate was 100%. Mean percent stenosis was 81%. The lesions were ostial in 28 patients, proximal in 10 patients and distal in 2 patients. In those patients having at least one year of follow up, the primary patency at one year was 93% (14/15). Hypertension was cured in 7 (20%) patients, improved in 17 (48.5%) patients and did not respond in 11 (31.5%) patients. Of 21 patients with disturbed renal function, 12 (57.2%) patients improved, 3 (14.3%) patients deteriorated and 6 (28.5%) patients were stabilized. CONCLUSION: Revascularization of renal artery stenosis is a simple, efficient and safe procedure with high primary technical results, low restenosis rates and acceptable complication rates. It has a beneficial effect on blood pressure control and a non-deleterious effect on renal function.